Silicon Application Differentially Modulates Root Morphology and Expression of PIN and YUCCA Family Genes in Soybean (Glycine max L.) - Tripathi, Pooja; Tayade, Rupesh; Mun, Bong-Gyu; Yun, Byung-Wook; Kim, Yoonha (Frontiers in Plant Science, 2022)
Silicon (Si) is absorbed and accumulated by some plant species, it has been shown to improve plant growth and performance. The beneficial role of Si in plants is based on fundamental assumptions and the biological function of Si is still being researched due to the complex nature, distinctiveness interaction. The present study included two distinct experiment sets: a screening test and an advanced test. In the initial examination, we used 21 soybeans (Glycine max L.) cultivars. Following the evaluation, we chose four cultivars to investigate further. In particular, positive response cultivars Taeseon and Geomjeongsaeol, showed a 14% increase in net photosynthesis and a 19%–26% increase in transpiration in Si-treated plants when compared to control plants. Si treated Taeseon, Geomjeongsaeol, and Somyongkong, Mallikong cultivars showed significant differences in root morphological traits (RMT) and root system architectural traits (RSA) when compared to control plants. Taeseon and Geomjeongsaeol showed a 26% and 46% increase in total root length (TRL) after Si application, respectively, compared to control, whereas Mallikong and Somyongkong showed 26% and 20% decreased TRL after Si treatment, respectively, compared to control. Si application enhanced overall RMTs and RSA traits in Taeseon and Geomjeongsaeol; however, the other two cultivars, Somyongkong and Mallikong, showed a decrease in such RMTs and RATs. Furthermore, to understand the underlying molecular mechanism and response of various cultivars we measured the Si content and analyzed gene expression of genes involved in auxin transport and root formation and development. We show that Si content significantly increased in Si-treated Somyongkong (28%) and Taeseon (30%) compared to the control cultivars. Overall, our results suggested that Si affects root development as well as genes involved in the auxin synthesis, transport pathway, modulates root growth leading to cultivar-dependent variation in soybeans.